Continuous Media with Microstructure 2 - Albers, Bettina; Kuczma, Mieczyslaw (Springer International Publishing : Imprint: Springer, 2016)
This book presents research advances in the field of Continuous Media with Microstructure and considers the three complementary pillars of mechanical sciences: theory, research and computational simulation. It focuses on the following problems: thermodynamic and mathematical modeling of materials with extensions of classical constitutive laws, single and multicomponent media including modern multifunctional materials, wave propagation, multiscale and multiphysics processes, phase transformations, and porous, granular and composite materials. The book presents the proceedings of the 2nd Conference on Continuous Media with Microstructure, which was held in 2015 in Łagów, Poland, in memory of Prof. Krzysztof Wilmański. .